2000
DOI: 10.1097/00008877-200011000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-induced conditioned place aversion in mice

Abstract: Previous studies have shown that ethanol produces conditioned place preference (CPP) in mice when injections are given immediately before exposure to the conditioned stimulus (CS). Paradoxically, however, injection of ethanol immediately after the CS produces conditioned place aversion (CPA). Four experiments were conducted to characterize the parametric boundaries of CPA produced by post-CS ethanol exposure. Experiment 1 showed that CPA is positively related to ethanol dose, with significant CPA at 2 and 4 g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 73 publications
6
57
1
Order By: Relevance
“…Conversely, After-S mice showed suppressed locomotor activity across conditioning days and on test. Although place preference data were not obtained, these conditioned locomotor effects are consistent with previous studies in DBA/2J mice in which the Before procedure produced CPP and the After procedure produced CPA (Cunningham and Noble, 1992;Cunningham et al, 1997;Cunningham and Henderson, 2000).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Conversely, After-S mice showed suppressed locomotor activity across conditioning days and on test. Although place preference data were not obtained, these conditioned locomotor effects are consistent with previous studies in DBA/2J mice in which the Before procedure produced CPP and the After procedure produced CPA (Cunningham and Noble, 1992;Cunningham et al, 1997;Cunningham and Henderson, 2000).…”
Section: Discussionsupporting
confidence: 90%
“…Ethanol-induced taste aversion conditioning has previously been shown by others to increase FOS expression in the nucleus of the solitary tract, the parabrachial nucleus, and the area postrema in subjects subsequently presented with an ethanol-paired tastant (Thiele et al, 1996). In light of data suggesting a genetic correlation between ethanol-induced conditioned taste aversion and ethanol-induced CPA (Cunningham and Ignatoff, 2000), it is possible that brain regions activated by the CS+ in the After-S group may have been missed by not examining FOS changes in the brain stem.…”
Section: Comparison Of Before and After Groupsmentioning
confidence: 90%
See 1 more Smart Citation
“…While this review integrates findings across both rats and mice, there may be some intrinsic biological differences in response to the reinforcing and aversive effects of ethanol existing between rats and mice. Ethanol-induced CPP is fairly well established among mouse literature (though notably lacking in the C57BL/6J mouse, the prototypical high-drinking strain; see Table 1), but the condition under which rats will exhibit an ethanol CPP remains unclear (Cunningham and Henderson, 2000;Fidler et al, 2004;Tzschentke, 1998). Fidler et al (2004) discusses the role route of administration plays on the development of CPP.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has also been proposed Cunningham and Henderson, 2000) that both CPP, conditioned place aversion, and CTA can be produced in the same animal by the same dose of ethanol simply by varying the timing of administration of the ethanol and the nature of the cues paired with ethanol delivery (gustatory or tactile/environmental). One recent study indicated a genetic correlation between CTA and place aversion conditioning wrought by injecting ethanol after exposure to the CS, suggesting that these two phenotypes can be related when measuring the aversive effects of ethanol (Cunningham and Ignatoff, 2000).…”
Section: Discussionmentioning
confidence: 99%